2016
DOI: 10.4103/0019-5049.174798
|View full text |Cite
|
Sign up to set email alerts
|

Does tranexamic acid reduce blood loss during head and neck cancer surgery?

Abstract: Background and Aims:Transfusion of blood and blood products poses several hazards. Antifibrinolytic agents are used to reduce perioperative blood loss. We decided to assess the effect of tranexamic acid (TA) on blood loss and the need for transfusion in head and neck cancer surgery.Methods:After Institutional Review Board approval, 240 patients undergoing supramajor head and neck cancer surgeries were prospectively randomised to either TA (10 mg/kg) group or placebo (P) group. After induction, the drug was inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 33 publications
1
41
1
Order By: Relevance
“…There are few studies in the literature about the use of TXA to reduce bleeding in malignant tumor surgical procedures [5][6][7][8]. Montroy et al published a meta-analysis in which lysine analogues examined the efficacy and safety of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are few studies in the literature about the use of TXA to reduce bleeding in malignant tumor surgical procedures [5][6][7][8]. Montroy et al published a meta-analysis in which lysine analogues examined the efficacy and safety of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…When some other cancer-related studies were examined, in a review investigating the effect of TXA administered during radical cystectomy for bladder cancer, TXA did not provide significant benefit compared to placebo [6]. In another study, it was reported that the use of TXA in head and neck cancers was not beneficial in reducing bleeding rates [7]. In another study examining the effect of TXA use in vertebral metastasis surgery, no significant benefit was reported in the amount of bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kulkarni et al . 9 conducted a double-blind, randomised study on 240 patients with head and neck cancers. They infused tranexamic acid or saline before the incision and repeated the infusion 3-hourly until wound closure commenced.…”
Section: Discussionmentioning
confidence: 99%